The funds concentration effect and discriminatory bailout - Erlenmaier, Ulrich; Gersbach, Hans (CESifo working papers, 2001)
In the presence of macroeconomic shocks severe enough to threaten the liquidity or solvency of the banking system, the regulator can rely on the funds concentration effect to save long-term investment projects. Some banks are forced into bankruptcy with the result that other banks obtain more new funds and remain solvent. We investigate two different implementations of the funds concentration effect and the corresponding discriminatory bailout scheme: random bailout and bailout the big ones. While the latter can be problematic in terms of stability, it is superior to the former in terms of welfare and credibility.
Keywords: Arbeitspapier; Graue Literatur; Unternehmenssanierung; Einlagensicherung; Bankenkrise; Konzentration; Fonds; Finanzintermediäre